Effect of miR‑215 on the Expression of Tumor Suppressor Gene Rb1 in Retinoblastoma Cell Lines - Liqin SHAO; Zhangxing SHENG; Yuefeng ZHU; Jianchao LI; Rufa MENG (Tehran University of Medical Sciences, 2020)
Background: Effect of miR-215 on the expression of tumor suppressor gene retinoblastoma (Rb)1 in Rb cell lines was investigated. Methods: A total of 128 patients were selected. The expression of miR‑215 in cancer and adjacent healthy tissues of the 128 patients was detected by reverse transcription-quantitative PCR (RT-qPCR). HXO‑Rb44 and Y79 cell lines were transfected with miR‑215 analogs or miR‑215 inhibitors, and the expression of Rb1 protein in the cell lines was detected by western blotting. Results: The expression of miR-215 in the adjacent healthy tissues of patients was significantly lower than that in cancer tissues (P<0.001). The expression of miR-215 in Y79 and HXO-Rb44 cells was significantly higher than that in APRE-19 cells (P<0.001). The expression of miR-215 in HXO-Rb44 cells was significantly higher than that in Y79 cells (P<0.001). The expression of miR-215 was statistically different from the degree of differentiation and nerve infiltration (P<0.05). The expression of Rb1 in cancer tissues was significantly lower than that in adjacent tissues (P<0.001), the expression of APRE-19 was significantly higher than that in Y79 and HXO-Rb44 cells (P<0.001), and the expression of Rb1 in HXO-Rb44 cells was significantly higher than that in Y79 cells (P<0.05). There was a negative correlation between miR-215 and Rb1 in the tissues of patients, and Rb1 expression decreased with the increase of miR-215 (r=-0.576, P<0.001). Conclusion: miR‑215 is highly expressed in Rb cell lines, and is related to the clinicopathological features of this disease.